Influence of Covid-19 Pandemic on Prenatal Care Utilization and Birth outcome - Qualitative Systematic Review Protocol (American Journal of Medical Science and Innovation, 2023)
The COVID pandemic disrupted routine prenatal care, yet little is known about expectant mothers’ experiences during this time. This qualitative systematic review aims to synthesize evidence on the experiences, views and impact of COVID on prenatal care utilization and birth outcomes. A systematic search is conducted in 5 databases and Google Scholar. Studies providing qualitative data on pregnant women’s experiences accessing prenatal care during COVID are included. Methodological quality is assessed using CASP and thematic synthesis is used to analyse the data. Even among these patients from affluent backgrounds, those who responded to the survey stated that the pandemic had significantly disrupted many parts of their daily lives and medical care, especially regarding social activities and postpartum support. Our findings make it clear that, in addition to increased support from healthcare systems, counseling on coping mechanisms and stressor adaptation techniques should be a part of perinatal care during public health emergencies for everyone. Results have provided an in-depth understanding of pregnant women’s experiences with barriers and facilitators to prenatal care during COVID, and the impact on maternal and neonatal outcomes. This review has identified recommendations to improve prenatal care access and quality during future health crises, contributing to more resilient and equitable maternity care systems.